2003
DOI: 10.1002/adma.200304889
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CO and O2 Using Tin Oxide Nanowire Sensors

Abstract: na powder (P172SB, PØchiney) with a specific area of 10.2 m 2 g ±1 , a refractive index of 1.70, and a mean diameter of 0.5 lm. A dispersant (phosphoric ester) is also used to decrease the viscosity and to increase the stability of the suspension. The final mixture is prepared with 80 wt.-% (50 vol.-%) of alumina, dispersant (1.5 wt.-% with respect to alumina) and photoinitiator (5.56 wt.-% with respect to the monomer) mixed in a ball mill for 20 min at 350 rpm.The scraper is based on a 10 mm long scalpel. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
647
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,044 publications
(664 citation statements)
references
References 27 publications
14
647
1
2
Order By: Relevance
“…11 The complexity and cost of fabrication as well as power consumption may hinder their applications. Komalkov et al 7 reported the O 2 and CO sensing properties based on an individual SnO 2 nanowire and a detection limit of a few 100 ppm for CO in dry air at 300°C was measured. Ultraviolet illumination was used to improve the sensitivity at room temperature.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 The complexity and cost of fabrication as well as power consumption may hinder their applications. Komalkov et al 7 reported the O 2 and CO sensing properties based on an individual SnO 2 nanowire and a detection limit of a few 100 ppm for CO in dry air at 300°C was measured. Ultraviolet illumination was used to improve the sensitivity at room temperature.…”
mentioning
confidence: 99%
“…Upon exposure to reductive gas species such as CO, the arrested electrons are released by the reactions between the reductive gas and the negatively charged ions: CO + O − → CO 2 + e − , reducing the steady-state surface oxygen concentration and donating a few electrons back to the bulk resulting in an increased conductivity. 7 Of these negatively charged ions, O − appears on tin oxide surface at a high temperature of about 150°C. 8 Most tin oxide gas sensors are effective only at temperatures above 200°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The insight gained from this study can advance our fundamental understanding of the optical behaviors of the technologically useful nanomaterials and, at the same time, promote the development of highly miniaturized, photonic and bio-optical devices utilizing the spatially controllable, optical responses of the individual semiconducting oxide NRs. [16][17][18][19][20][21][22][23][24] In many of these technologically important applications, the fundamental optical properties of 1D SO nanomaterials govern their functional outcomes. Light can produce various optical and optoelectronic responses from the materials and, therefore, light-matter interactions can be engineered to produce desirable optical properties such as spontaneous and stimulated emission, 1,25-29 waveguiding, 1-3 and evanescence field enhancement.…”
mentioning
confidence: 99%
“…One-dimensional (1D) nanomaterials based on semiconducting oxides (SOs) have demonstrated their useful properties in numerous applications of photonics, 1-4 electronics, [5][6][7][8] optoelectronics, 9,10 photovoltaics, [11][12][13][14][15] and chemical/biological sensing. [16][17][18][19][20][21][22][23][24] In many of these technologically important applications, the fundamental optical properties of 1D SO nanomaterials govern their functional outcomes. Light can produce various optical and optoelectronic responses from the materials and, therefore, light-matter interactions can be engineered to produce desirable optical properties such as spontaneous and stimulated emission, 1,25-29 waveguiding, 1-3 and evanescence field enhancement.…”
mentioning
confidence: 99%